Does immigration fosters the Algerian exports? A Static and Dynamic Analysis - Lamara Hadjou (European Regional Science Association (ERSA), 2015)
Algeria has a large immigrant population. It is the third largest African community in the world after that of Egypt and Morocco. Its role in the international trade of Algeria has never been object of evaluation study. In line with the recent literature developed since the 1990s, through the work of Gould (1994), on the relationship between immigration and international trade, we propose in this paper to assess the impact of Algerian immigration networks on Algerian exports. It is clear that immigrants represent an opportunity for diversification and intensification of Algerian exports. However, the involvement of immigrants in trade flows is not evident. It is then necessary to assess first the impact and degree of involvement, to propose later, elements of trade policy that can improve the impact.
Keywords: F22; F1; 330; immigration; export; Algeria